Ellagitannins with Glucopyranose Cores Have Higher Affinities to Proteins than Acyclic Ellagitannins by Isothermal Titration Calorimetry - Karonen M.; Oraviita M.; Mueller-Harvey I.; Salminen J.-P.; Green R.J. (AMER CHEMICAL SOC, 2022)
The thermodynamics of the interactions of different ellagitannins with two proteins, namely, bovine serum albumin (BSA) and gelatin, were studied by isothermal titration calorimetry. Twelve individual ellagitannins, including different monomers, dimers, and a trimer, were used. The studies showed that several structural features affected the interaction between the ellagitannin and the protein. The interactions of ellagitannins with proteins were stronger with gelatin than with BSA. The ellagitannin-gelatin interactions contained both the primary stronger and the secondary weaker binding sites. The ellagitannin-BSA interactions showed very weak secondary interactions. The ellagitannins with glucopyranose cores had stronger interaction than C-glycosidic ellagitannins with both proteins. In addition, the observed enthalpy change increased as the degree of oligomerization increased. The stronger interactions were also observed with free galloyl groups in the ellagitannin structure and with higher molecular flexibility. Other smaller structural features did not show any overall trend.